Real-time voxelized mesh fracture with Gram–Schmidt constraints - McGraw, Tim; Zhou, Xinyi (Computers & graphics, 2025)
Much previous research about fracture of deformable bodies has focused on physical principles (e.g. energy and mass conservation), leading to simulation methods that are very realistic, but not yet applicable in real-time. We present a stylized animation method for destruction of soft bodies that is visually plausible and capable of running at hundreds of frames per second by sacrificing visual realism and physical accuracy. Our method uses a new volume-preserving voxel constraint based on Gram–Schmidt orthonormalization which, when used in tandem with a breakable face-to-face voxel constraint, allows us to animate destructible models. We also describe optional LOD constraints which speed convergence and increase apparent stiffness of the models. The creation pipeline and constraints presented here are designed to minimize the number of partitions needed for parallel Gauss–Seidel iterations. We compare the proposed techniques with shape constraints and the state-of-the-art material point method on the basis of memory usage, computation time and visual results. [Display omitted] •Destructible models in a voxelized visual style are created from watertight meshes.•Position-based dynamics constraints are based on Gram–Schmidt orthonormalization.•Model structure permits an efficient parallelization scheme.•LOD constraints speed up convergence efficiently.